2015
DOI: 10.1124/jpet.115.227025
|View full text |Cite
|
Sign up to set email alerts
|

Cracking the Egg: Potential of the Developing Chicken as a Model System for Nonclinical Safety Studies of Pharmaceuticals

Abstract: The advance of perinatal medicine has improved the survival of extremely premature babies, thereby creating a new and heterogeneous patient group with limited information on appropriate treatment regimens. The developing fetus and neonate have traditionally been ignored populations with regard to safety studies of drugs, making medication during pregnancy and in newborns a significant safety concern. Recent initiatives of the Food and Drug Administration and European Medicines Agency have been passed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 138 publications
(138 reference statements)
0
39
0
Order By: Relevance
“…In addition, some mouse models to date have had to specifically utilize immunocompromised strains to allow for ZIKV infection, as common strains systemically infected with ZIKV have no microcephalic phenotype ( Cugola et al, 2016 ). The innate immune system of the chick embryo does not function until around E14 ( Kain et al, 2014 ) suggesting that this in vivo system provides a naturally immunodeficient model system suitable for both human xenografts as well as viral infection ( Bjornstad et al, 2015 ). We intracranially injected hiNSCs into developing chick embryos, subjected them to systemic ZIKV infection and found that humanized ZIKV-infected embryos developed severe microcephaly consisting of significantly reduced cranial size, decreased forebrain volume and enlarged ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some mouse models to date have had to specifically utilize immunocompromised strains to allow for ZIKV infection, as common strains systemically infected with ZIKV have no microcephalic phenotype ( Cugola et al, 2016 ). The innate immune system of the chick embryo does not function until around E14 ( Kain et al, 2014 ) suggesting that this in vivo system provides a naturally immunodeficient model system suitable for both human xenografts as well as viral infection ( Bjornstad et al, 2015 ). We intracranially injected hiNSCs into developing chick embryos, subjected them to systemic ZIKV infection and found that humanized ZIKV-infected embryos developed severe microcephaly consisting of significantly reduced cranial size, decreased forebrain volume and enlarged ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…MMI treatments were initiated at E14, during the pseudoglandular stage of lung development, when several developmental steps, including most of the proximal-distal differentiation and preparabronchial vascularization, have already taken place [16]. Our model is therefore most relevant in exploring regulatory mechanisms involved in developmental events in the atrioinfundibular (equivalent to human canalicular, 16-24 weeks of gestation) and air-capillary (equivalent to human saccular, 24 weeks of gestation to term) [7] stages of lung development, including distal epithelial and vascular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The chicken has a long history as a developmental model system [7]. Verhoelst et al [8] demonstrated that methimazole (MMI) administration to developing chicken fetuses at embryonic day (E)14 at doses of 2.0 mg/egg induces hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Chicken embryo has been a model organism for developmental biology for a very long time . It is expansively studied in fields of developmental biology , cardiovascular studies , and angiogenesis .…”
Section: Introductionmentioning
confidence: 99%